AZF microdeletion affects semen parameters, sex hormone levels, and chromosome karyotypes in infertile men in Xinjiang: Effects of AZF microdeletion on male infertility-related factors - Han, Ningning; Liu, Xiaoran (Cellular and Molecular Biology, 2023)
This study aimed to analyze the correlation between the microdeletion of different regions of the azoospermia factor (AZF) gene and semen parameters, sex hormone levels, and karyotypes in infertile males by retrospective study. This was performed to obtain a comprehensive understanding of the clinical data of AZF microdeletion in infertile males, to guide clinical diagnoses and treatments, and to improve the efficacy and safety of assisted reproductive technology. For this purpose, Fifty-seven patients with AZF microdeletions and complete data were selected from 1916 patients with AZF microdeletions in our hospital from January 2020 to August 2022. The correlation between semen parameters, sex hormone levels, and chromosome karyotypes of these 57 patients was analyzed. Results showed that among the 57 patients with AZF microdeletions, the region with the highest microdeletion rate was AZFc with 57.89%; single or combined deletions in AZFa and AZFb regions resulted in azoospermia. The deletion frequency of AZFc in the oligospermia group was significantly higher than that in the azoospermia group, and the deletion frequencies of AZFb and AZFb + c in the azoospermia group were significantly higher than those in the oligospermia group (P<0.05). There were statistically significant differences in follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, and chromosome karyotypes between patients with azoospermia and oligospermia (P<0.05). Statistically significant differences were observed in prolactin (PRL), FSH, testosterone (T), LH levels, and chromosome karyotypes of patients in different AZF microdeletion regions (P<0.05). In conclusion, AZF microdeletions can lead to a decline in semen quality in men, and different types of deletions have different effects on semen parameters, sex hormone levels, and karyotype analysis. Further treatments should be selected based on the AZF microdeletion area.